2008
DOI: 10.1111/j.1748-0361.2009.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Cancer Screening in Older American Indian and Alaska Native Men

Abstract: However, the case mortalities for colorectal and prostate cancers among AI men in the Northern Plains exceed those for US men of all racial/ethnic populations by 59% and 48%, respectively.Recent studies have linked obesity with cancer, including colorectal and prostate cancer. [3][4][5] In the United States, 67% of all adult men and 77% of AI adult men are overweight/obese.6 Obesity is associated with decreased access to care and lower rates of some cancer screening behaviors. 7,8 The influence of obesity on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…All other studies were regional, state-based, or local. Three studies included white subjects predominantly (29, 30, 41), two studies included only black subjects (33, 39), a single study included only Latino subjects (43), and another study included only Native American men (38). All other studies (N=16) were multi-ethnic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All other studies were regional, state-based, or local. Three studies included white subjects predominantly (29, 30, 41), two studies included only black subjects (33, 39), a single study included only Latino subjects (43), and another study included only Native American men (38). All other studies (N=16) were multi-ethnic.…”
Section: Resultsmentioning
confidence: 99%
“…All studies reported BMI as the measure of adiposity. Two studies used fecal occult blood testing as the sole component of their screening definition (33, 38); the remainder included sigmoidoscopy or colonoscopy or both.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies were identified that examined the relationship of obesity and colorectal cancer (CRC) screening [22, 24, 3243, 48, 49], but only six studies stratified the obesity-cancer screening relationship by gender [35, 36, 39, 40, 42, 43]. In men, the relationship between obesity and CRC screening was inconsistent.…”
Section: Resultsmentioning
confidence: 99%